Chapter 4. Peptidases of trematodes - Kasný, Martin; Mikes, Libor; Hampl, Vladimír; Dvorák, Jan; Caffrey, Conor R; Dalton, John P; Horák, Petr (Advances in parasitology, 2009)
Among human and veterinary parasitic diseases the trematodiases (e.g. schistosomiasis, fascioliasis) represent a problem of global importance with vast social, economic and public health impacts, especially in developing countries. Therefore, host-parasite (host-trematode) interactions represent a key topic in many research laboratories, and modern approaches and technologies allow us to study the molecular basis of these interactions. As a consequence, key molecules produced by trematodes in order to ensure parasite invasion and survival within a hosts can be characterized. Trematode peptidases certainly belong to such molecules; as they are indispensable biocatalysts in a number of basal biological processes in trematodes (e.g. tissue invasion/migration, nutrition, immune evasion or other host-parasite interactions). Schistosoma mansoni cercarial elastase (CE) (penetration enzyme), cathepsin B (CB) (mainly nutrition enzyme) and Fasciola hepatica cathepsin L (CL) (nutrition, immune evasion enzyme) are probably the most studied trematode peptidases with well-characterized critical functions. Due to the importance of peptidases in host-parasite interactions they are considered to be promising targets for the development of novel chemotherapeutic drugs and vaccines against a number of trematodiases, including schistosomiasis, fascioliasis, paragonimiasis and opisthorchiasis. The present chapter summarizes the data on the biochemical and molecular features of the major trematode peptidases, and describes their role in trematode biology and host-parasite interactions based on proteolysis (peptidolysis).
Keywords: proteasy; infekce červy třídy Trematoda; Host-Parasite Interactions; Trematoda; zvířata; Peptide Hydrolases; lidé; Humans; Trematode Infections; interakce hostitele a parazita; Virulence Factors; Animals; faktory virulence